The ABCs of artificial antigen presentation - Kim, Jiyun V; Latouche, Jean-Baptiste; Rivière, Isabelle; Sadelain, Michel (Nature biotechnology, 2004)
Artificial antigen presentation aims to accelerate the establishment of therapeutic cellular immunity. Artificial antigen-presenting cells (AAPCs) and their cell-free substitutes are designed to stimulate the expansion and acquisition of optimal therapeutic features of T cells before therapeutic infusion, without the need for autologous antigen-presenting cells. Compelling recent advances include fibroblast AAPCs that process antigens, magnetic beads that are antigen specific, novel T-cell costimulatory combinations, the augmentation of therapeutic potency of adoptively transferred T lymphocytes by interleukin-15, and the safe use of dendritic cell-derived exosomes pulsed with tumor antigen. Whereas the safety and potency of the various systems warrant further preclinical and clinical studies, these emerging technologies are poised to have a major impact on adoptive T-cell therapy and the investigation of T cell–mediated immunity.